Studies the growth parameters of Nd3+ doped yag crystal - Sahar, Md Rahim; Ismail, Ervezan; Rohani, Md. Supar (Faculty of Science, University Teknologi Malaysia, 2008)

(untitled)
The nd:yag crystal with the dimension of 65 mm in length and 30 mm in diameter has successfully been grown by czochralski technique using the automatic diameter control ? Crystal growth system (adc-cgs) software in an argon gases atmosphere. The crystal grown is light purple when exposed to the light. The crack is found at the bottom part of crystal